Analisis Pengaruh Dari Overbelasting Terhadap Penegakan Hukum Pidana Pada Polda Yogyakarta - Felia Hermayenti (Darma Cendika Catholic University, 2026)
Indonesia is a country with numerous laws and regulations governing various sectors of public life. Most of these regulations contain criminal sanctions as an enforcement instrument, resulting in a growing number of acts potentially categorized as criminal offenses. This situation also encourages high public enthusiasm for reporting various acts deemed unlawful to law enforcement officials. The numerous criminal provisions scattered across various laws and regulations, coupled with the high volume of public reports, ultimately have the potential to create an excessive workload (overload) for police officers as law enforcers, which is feared to have an impact on reducing the effectiveness and quality of law enforcement itself. Based on these problems, this research was designed to answer three problem formulations.First, is it true that there has been an excessive workload at the Yogyakarta Regional Police (Polda)?Second, to what extent does the excessive workload affect the quality of law enforcement carried out by the police.Third, what factors cause this excessive workload. To answer these three research questions, this study uses an empirical legal research method, with the research location being the Yogyakarta Regional Police.